PILIHAN ENERGI MASA DEPAN UNTUK INDONESIA: FUTURE ENERGY OPTIONS FOR INDONESIA - Agustinus Denny Unggul Raharjo (JISTECH: Journal of Information Science and Technology, 2014)
As the largest nation in Southeast Asia Indonesia have major problems in energy consumption. Most of Indonesia energy consumption goes to supplied the high density populous area of Java Island, thus the infrastructures of energy storage and distribution is much more advanced in Java Island compare to other islands. Blessed by bountifull energy resources the nation primarily depended on fossil fuel energy for the last 30 years. In recent times, as import for fossil fuel energy increased, utilization of other source of energy are developed. Into the future the nation most likely would depend on energy from natural gas and renewable resources such as geothermal and hydroelectric to reduce the consumption of fossil fuel energy.